Supraneural transforaminal epidural injection in the treatment of radiculopathy in the lumbar spine – a brief descriptive overview and technique of manipulation - D. A. Averyanov; K. N. Khrapov (Вестник анестезиологии и реаниматологии, 2023)
Fluoroscopy guided epidural injection is often used to treat radicular pain in the lumbar spine. Risk and effectiveness data vary depending on injection routes and underlying pathology. There are several options for accessing the epidural space in the lumbosacral spine to perform an analgesic injection – caudal, interlaminar and transforaminal. Transforaminal epidural injection is currently the most studied and widespread in the foreign practice of treating chronic pain. A brief overview describes transforaminal accesses to the epidural space of the lumbar spine and needles used for this purpose, lists possible adverse events and complications, and also provides a detailed illustrated description of supraneural transforaminal access.